Pengaruh Rotasi Kerja terhadap Kinerja Pegawai Dimediasi dengan kepuasan Kerja pada Pegawai DISPORA Kabupaten Gresik - Sarah Adilla; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Many factors can trigger employee job dissatisfaction, such as boredom or boredom at work, so job rotation also triggers employee job satisfaction. This study aims to analyse the effect of job rotation on employee performance mediated by job satisfaction at the government office. The type of research selected in this study is quantitative. The sampling technique used a saturated sample, including 38 government office employees as respondents. Data were collected by questionnaire. The data analysis technique used is the structural equation model (SEM) with the partial least squares (PLS) by SmartPls 3.3.3. This study explains that job-rotation influences employee performance and job satisfaction, but the effect of job satisfaction on employee performance does not have a significant impact. Job satisfaction does not mediate the effect of job rotation on employee performance. Concerning job rotation, it is expected that job rotation is carried out regularly and in a planned manner. The implication of this research is that job rotation is necessary for the organisation to improve the performance and satisfaction of its employees. Then, employee performance is not always influenced by job satisfaction because the version produced by employees is one of the obligations that employees must carry out.